Simulation of the water balance through geomatics in the Cañete river basin (Aporte Santiaguino, 2024)
The water problem has a negative impact on the economic income of producers. The main objective of this article is to evaluate the simulation of the water balance through geomatic simulation in the Cañete River basin. The real value was roughly calculated using geomatic simulation with ArGis software. The approach is quantitative, applied type and non-experimental design. The water balance in the Cañete River was determined using the Hargreaves method and the Thomthwaite method. Based on evapotranspiration, precipitation, mean temperature, minimum and maximum temperature were calculated. The same variables were taken as variables and the Cañete river basin as shown. The data collection techniques applied are documents and records obtained from the Senamhi database. A 10-year projection was made for water to be sustainable over time.
Keywords: Simulation; Water balance; Geomatics; Cañete river; Water